Production networks and industrial clusters : integrating economies in Southeast Asia - Kuroiwa, Ikuo; Toh, Mun Heng (Gale virtual reference library, 2008)
Explains how production networks and industrial clusters have played crucial roles in the industrial development of Indonesia and Malaysia (electronics industry), Singapore (biomedical science industry), and Thailand (automotive industry).